UN SIGLO UTILIZANDO TESTS - Navas, María José (R.E.M.A. Revista electrónica de metodología aplicada, 2012)
The aim of this work is to think about tests in current society. In order to do that, some ideas related to the origin and development of tests are first highlighted. Then, issues regarding the usual areas of application of tests and the multiple functions they serve are dealt with. Next, there is a more detailed presentation of the more frequent critiques that tests have been suffering since the end of the 20s. The focus is on the heated debate on fairness and tests and on the misuse of tests. Finally, a few words are said about the future of tests and testing.